The Role of Job Satisfaction Mediation in the Work Environment and Employee Performance - Febryan, Sandy; Kamilia, Nurul (Research Horizon, 2025)
This research seeks to examine how the work environment affects employee performance, using job satisfaction as a mediating factor. The research issue arises from the observed gap between the working environment conditions that fulfill the standards and the decrease in employee performance at the manufacturing firm PT. Assemble a group of individuals. Employing an explanatory quantitative method, this research examined the connection among variables utilizing data from 158 participants through the Structural Equation Modeling (SEM) technique founded on Partial Least Square (PLS). The analysis results indicate that the work environment positively and significantly influences employee performance and job satisfaction. Job satisfaction has been demonstrated to significantly impact performance and serves as a mediator that enhances the connection between the work environment and performance. Therefore, job satisfaction serves as a crucial avenue for enhancing the effects of the work environment on employee productivity. These results validate that managing the work environment and enhancing job satisfaction are essential approaches to boost human resource performance